Quad-Band U-Slot Antenna for Mobile Applications - Palmero, Eduardo de las Heras; Raida, Zbynek; Ruiz, Roberto Lamadrid (Radioengineering Society, 2006)
In this paper, two different planar quad-band antennas are designed, modeled, fabricated and measured. Subsequently, the antennas are redesigned using an electromagnetic band gap substrate (EBG). Those new planar antennas operate in four frequency bands: 900 MHz, 1 800 MHz (both GSM), 1 900 MHz (USA) and 2 400 to 2 500 MHz (Bluetooth) The antenna has four narrow U-shaped slots etched to the patch. Using software, CST Microwave Studio [1], Zeland IE3D [2], and FEMLAB [3], simulations have been carried out to investigate the antenna\'s performance and characteristics. The antennas designed have been also built and measured to compare the real results with those obtained from the simulations.
Keywords: Multi-band planar antennas; perturbation slots; modal analysis; full-wave analysis; GSM; Bluetooth. EBG substrates